Petrified intelligence : nature in Hegel's philosophy - Stone, Alison, 1972- (SUNY series in Hegelian studies., 2005)
"Petrified Intelligence offers the first comprehensive treatment of Hegel's Philosophy of Nature, exploring its central place within his system, including its relation to his Logic, Philosophy of Mind, and moral and political thought. It highlights the contemporary relevance of Hegel's approach to nature, particularly with respect to environmental issues. Challenging the standard view that Hegel devalues nature relative to mind and culture, Alison Stone reveals the deep concern to re-enchant the natural world that pervades his entire philosophical project. Written in clear and nontechnical language, the book also provides a critical introduction to Hegel's metaphysics."--Jacket.